TRANSFORMASI KESETARAAN GENDER DALAM KRITIK SASTRA ARAB FEMINIS: SEBUAH REKONSTRUKSI EPISTEMOLOGIS - Rusydi, Muhammad (An - Nisa`, 2015)
Gender equity among men and women is a noble concept that must transformed into feminism Arabic literature critique that is expected to be an alternative media for the fight of the gender equity. In its implementation, the epistemology construction of feminism Arabic literature critique consisting of source, structure, method, and validity has not transformed the gender equity maximally. Consequently, epistemology reconstruction must be developed towards feminism Arabic literature critique in which the fight concept of gender equity consisted in its source, structure, method, and validity is reconstructed by accommodating all possibilities relating to the concept without leaving the existing ones